2011
DOI: 10.3399/bjgp11x613124
|View full text |Cite
|
Sign up to set email alerts
|

Primary care access and its relationship with emergency department utilisation: an observational, cross-sectional, ecological study

Abstract: BackgroundRecent health service policies in the UK have focused on improving primary care access in order to reduce the use of costly emergency department services, even though the relationship between the two is based on weak or little evidence. Research is required to establish whether improving primary care access can influence emergency department attendance. AimTo ascertain whether a relationship exists between the degree of access to GP practices and avoidable emergency department attendances in an inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
4
5

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 13 publications
5
61
4
5
Order By: Relevance
“…It is also worth noting that the relationship between poor perceived access to general practice and high use of EDs has not always been found. 56 This is also true for its relationship with emergency admissions. 20 …”
Section: Four-hour Targetmentioning
confidence: 98%
“…It is also worth noting that the relationship between poor perceived access to general practice and high use of EDs has not always been found. 56 This is also true for its relationship with emergency admissions. 20 …”
Section: Four-hour Targetmentioning
confidence: 98%
“…Harris et al (2011) conduct a cross-sectional ecological study of one Primary Care Group, whereby they test whether ED attendance can be explained by varying accessibility to GP practices proxied by total opening hours per week. None of the proxies for accessibility turns out significant, thus suggesting that the use of the ED is probably driven by the underlying characteristics of users, including that of social deprivation.…”
Section: Background Literaturementioning
confidence: 99%
“…17 Our results agree with numerous other studies reporting low socioeconomic status contributing to an increased use of the ED. 3,9,10,14,17,18 However, what our study adds is that it also leads to a decrease in use of ED alternatives.…”
Section: In Context Of Current Literaturementioning
confidence: 68%
“…[7][8][9][10] Evidence suggests that ED overcrowding is associated with adverse clinical outcomes, [10][11][12] and proposed solutions have ranged from streamlining inpatient admissions to expanding primary care. [13][14][15] It is important to understand the current patterns of ED use if primary health care initiatives are to effectively reduce ED workloads and improve overall health. Jones et al in a before/after study found that an after-hours urgent care clinic reduced the number of those seeking care in the ED.…”
Section: Résumémentioning
confidence: 99%